Fungsi Pemahaman Akuntansi, Program Pelatihan, dan Pemanfaatan Teknologi Informasi Terhadap Efektivitas Sistem Informasi Akuntansi UMKM - Syafira Putri Aliefia; Lesi Hertati; Lili Syafitri (CV. Ulil Albab Corp, 2024)
The study aims to understand the impact of accounting understanding, training programmes and the use of information technology on the effectiveness of the accounting information system. This research was carried out on the entire UMKM in the Sako Palembang district. Sampling is based on probability sampling techniques that are simple random samplings with a selected sample of 96 respondents. This research data is obtained from a questionnaire (primary data). The analysis technique used in this study is a double linear regression method. Data analysis results with Statistical Product and Service Solutions (SPSS) Version 26. Based on the results of the test, F referred to the Value of Computing (X1), Training Program (X2) and Use of Information Technology (X3) with a value of Ftable of 2,473 so that the value of computing > Ftable (164,389 > 2,473) with the significance of 0,000 > 0,05 then it can be concluded that the Effectiveness of Accounting Information Systems (Y) is 0,000 < 0,05 and the counting value of t > table is 5.015 > 1,9886.